2020
DOI: 10.4018/jeco.2020070101
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic and Utilitarian Values Behind Engagement of Online Consumers

Abstract: In the hyper-competitive Indian airline industry, the low-cost carriers as well as full-service airlines are in dire need of innovative marketing strategies to engage their customers. To understand the dynamics behind the process of customer engagement, the purpose of this paper is to gain insights into the lived experience of consumers about their online air-ticket bookings experiences. In total, 60 frequent air travellers were approached to participate in the study and the self-completion diary method was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In the UTAUT2 model, Venkatesh et al [31] explained that habits reflect how consumers tend to act in a structured manner, which results from repeated learning; this means that behavior is influenced by repetitive activities that become habits. Previous research has shown that habit influences adoption behavior [55]. Moreover, research conducted by Chang et al [54] mentioned that a consumer's habit has an impact on use behavior significantly.…”
Section: Hypothesis 5 (H5) Hedonic Motivation Positively Influences mentioning
confidence: 99%
See 1 more Smart Citation
“…In the UTAUT2 model, Venkatesh et al [31] explained that habits reflect how consumers tend to act in a structured manner, which results from repeated learning; this means that behavior is influenced by repetitive activities that become habits. Previous research has shown that habit influences adoption behavior [55]. Moreover, research conducted by Chang et al [54] mentioned that a consumer's habit has an impact on use behavior significantly.…”
Section: Hypothesis 5 (H5) Hedonic Motivation Positively Influences mentioning
confidence: 99%
“…Hedonic motivation is the preferred desire in the use of technology, and this has proven to be a determining factor in the process of recognizing and adopting new technology [47,54]. Research by Zeba et al [55] proved that hedonic motivation was able to adopt consumers towards the online purchasing process in the case of the airline industry. In addition, hedonic motivation is also an intrinsic factor that makes technology users like FinTech cognitively attached to a platform [51].…”
Section: Hypothesis 4 (H4) Facilitation Conditions Have a Positive Ementioning
confidence: 99%
“…The customer generally visits an online shopping website with a hedonic or utilitarian motive (Arnold & Reynolds, 2003; Bridges & Florsheim, 2008; Krithika & Rajini, 2017; Papacharissi & Rubin, 2000; Wildeboer & Donkers, 2014; Zeba et al, 2020). Customers with hedonic motives are involved in shopping for experiences related to fun and pleasure (Zeba et al, 2020).…”
Section: Stages Of Online Purchase—motives and Challengesmentioning
confidence: 99%
“…The customer generally visits an online shopping website with a hedonic or utilitarian motive (Arnold & Reynolds, 2003; Bridges & Florsheim, 2008; Krithika & Rajini, 2017; Papacharissi & Rubin, 2000; Wildeboer & Donkers, 2014; Zeba et al, 2020). Customers with hedonic motives are involved in shopping for experiences related to fun and pleasure (Zeba et al, 2020). Table 3 depicts a summary of the various experiences that customers can have from online shopping such as idea shopping, value shopping, gratification shopping, and adventure shopping (Arnold & Reynolds, 2003).…”
Section: Stages Of Online Purchase—motives and Challengesmentioning
confidence: 99%
“…Consumers' perceived consumption values play crucial role in shaping consumer behavioural intention (Shankar and Jain, 2021). Hence, in prior literature, several studies determined the positive effects of consumption values on consumer behavioural intention in several contexts (Mohd-Any et al, 2014 ;Mäntymäki and Salo, 2015;Carlson et al, 2015;Dhir et al, 2018;Kaur et al, 2018;Jang et al, 2019;Talwar et al, 2020;Shankar and Jain, 2021;Zeba et al, 2020;Thanigan et al, 2021). Different types of consumption values namely, functional value, emotional value, social value, conditional value, and epistemic value plays crucial role in framing consumer behavioural intention (Sheth, 1991;Talwar et al, 2020).…”
Section: Impact Of Perceived Consumption Values On Adoption Intentionmentioning
confidence: 99%